Molecular Detection of mecA and aac(6’)-aph(2”) Genes in Staphylococcus aureus Isolates from Clinical Specimens (Tribhuvan University Journal of Microbiology, 2023)
Objectives: The main aim of this study is to assess the prevalence of Staphylococcus aureus in clinical samples and its antimicrobial susceptibility pattern based on the detection of mecA and aac(6’)-aph(2”) genes conferring resistant ability to S. aureus isolates.Methods: A prospective hospital based cross-sectional study was conducted among the patients visiting Kirtipur hospital for 6 months from May 2020 to November 2020. The clinical samples were collected and processed for culture and identified following standard microbiological procedures. Antibiotic sensitivity testing was performed by Kirby Bauer disc diffusion method and methicillin resistance was determined by using cefoxitin (30 μg) disc and interpreted as per CLSI guidelines. The chromosomal and plasmid DNA were extracted and aac(6’)-aph(2”) and mecA genes were detected by conventional polymerase chain reaction.Results: Out of 1969 clinical samples, the overall prevalence of S. aureus was 9.82% and among the staphylococci, 50(75.8%) were MRSA. Male patients from 31-45 age group and those visiting OPD were more prone to MRSA infection, although only patient’s status and age group were statistically significant. Most of the MRSA were recovered from wound swab (78.2%). A majority of the MRSA isolates were resistant to Ciprofloxacin (90%). Similarly, resistance to Gentamicin was observed in only 12(24%) isolates. Resistance to Gentamicin was statistically associated with types of samples but not with gender, age group and patient status. Among the 50 MRSA isolates, 10 were identified as co-harboring both the aac(6’)-aph(2”) and mecA genes. Notably, excluding only 2 MRSA isolates, the remaining 48 isolates demonstrated the presence of the mecA gene.Conclusion: High prevalence of MRSA in this study underscores the need for more commitment towards infection control measures that meet the standard protocols aimed at reducing the spread of infection by MRSA among susceptible individuals.